Aplikasi Game Edukasi Mengenal Bahasa Indonesia Alfabert dengan Algoritma Ascent Hill Climbing - Megi Afroka; Yosdarso Afero (STMIK Budi Darma, 2022)
Alphabet learning educational game is a game that is very popular with children who are new to Alphabet letters. This game uses the process of exchanging the position of the alphabet according to the correct alphabetical order. The problem in this study is the lack of interest in children learning the alphabet quickly, with the game system children who know the alphabet are happier and quickly understand the order of the alphabet. The benefit of this research is to improve the thinking power and creative patterns of children who are new to the alphabet quickly to catch how to memorize the alphabet correctly. This study uses the Ascent Hill Climbing Algorithm. How the Ascent Hill Climbing Algorithm works, namely a. The basic rule that must be done is to move an empty square to the top of the puzzle where if x>1 then (x-1,y) b. The basic rule that must be done is to move the empty square down Puzzle if x<3 then (x+1,y c. The basic rule to be done is to move the empty square to the right Puzzle if x<3 then (x+1,y) d The basic rule that must be done is to move the empty square to the left of the Puzzle if x>1 then (x,y-1). The final result of this study is that it takes 8 iterations to obtain the correct position for compiling the Puzzle so that it matches the goal state order so that the results are finished and terminated.